STIHL Timbersports® and the Reconceptualization of Modern Sport in the Light of Decontextualization and Eventification of Forestry Work - Bo Carlsson; Isak Lidström; Leif Yttergren (Social Sciences, 2022)
This article examines STIHL Timbersports® and its amalgamation of craftmanship, competition, eventification and branding, through the lens of decontextualization of sport. It thus revisits and revitalizes the concept of sportification, as well as discusses the characteristics of sport such as authenticity and “uncertainty of outcome”. The aim of the article is to grasp the different processes that challenge our common positions regarding sport, which may in turn progress sport beyond the prevalent conceptualization of modern sport.